O conceito fundamental de mundo na construção de uma ontologia da geografia - Gallo, Priscila Marchiori Dal; Marandola Junior, Eduardo (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2015)
The construction of a geographic thought from the phenomenology unfolded in the effort of revision of its fundamental concepts, especially, from the point of view of the ontology. In this context, to ask itself for the constitution of the world concept becomes indispensable to operate it since an original geographic experience and to institute it as an original happen whose foundation is the strife Earth-world. For this we appeal to the Heidegger’s discussion on the origin of the work of art, which establishes the correspondence between the truth (as unveiling) and the work of art for the understanding of the constitution of the world as opening of an ontological horizon as an spacing out happen